Implementasi Filsafat dalam Pendidikan Karakter Religius di MTs NU Raudlatul Muallimin - Firdiana, Linda; Mujiburrohman, Mujiburrohman (TSAQOFAH, 2025)
This study aims to describe the implementation of philosophical values in religious character education through the habitual recitation of Istighotsah and the Qur’an at MTs NU Raudlatul Muallimin. The research focuses on how values such as self-awareness, moral development, and spiritual strengthening are internalized through routine religious practices within the school environment. A qualitative approach with a case study design was employed. Data were collected through direct observation, interviews with teachers, and documentation of daily religious activities. The findings reveal that the practice of reciting Istighotsah and the Qur’an not only reinforces students’ spiritual dimensions but also instills philosophical values such as patience, submission to God, and moral responsibility. These activities serve as effective mediums for cultivating students’ ethical awareness in daily life. The study concludes that integrating religious practices with a philosophical approach can foster students’ religious character in a reflective and sustainable manner, and makes a significant contribution to strengthening character education values in madrasah settings.